Early indicators of disease progression in Fabry disease that may indicate the need for disease-specific treatment initiation: findings from the opinion-based PREDICT-FD modified Delphi consensus initiative. Issue 10 (10th October 2020) - Hughes, Derralynn A; Aguiar, Patricio; Deegan, Patrick B; Ezgu, Fatih; Frustaci, Andrea; Lidove, Olivier; Linhart, Aleš; Lubanda, Jean-Claude; Moon, James C; Nicholls, Kathleen; Niu, Dau-Ming; Nowak, Albina; et al.
Abstract : Objectives: The PRoposing Early Disease Indicators for Clinical Tracking in Fabry Disease (PREDICT-FD) initiative aimed to reach consensus among a panel of global experts on early indicators of disease progression that may justify FD-specific treatment initiation. Design and setting: Anonymous feedback from panellists via online questionnaires was analysed using a modified Delphi consensus technique. Questionnaires and data were managed by an independent administrator directed by two non-voting cochairs. First, possible early indicators of renal, cardiac and central/peripheral nervous system (CNS/PNS) damage, and other disease and patient-reported indicators assessable in routine clinical practice were compiled by the cochairs and administrator from panellists' free-text responses. Second, the panel scored indicators for importance (5-point scale: 1=not important; 5=extremely important); indicators scoring ≥3 among >75% of panellists were then rated for agreement (5-point scale: 1=strongly disagree; 5=strongly agree). Indicators awarded an agreement score ≥4 by >67% of panellists achieved consensus. Finally, any panel-proposed refinements to consensus indicator definitions were adopted if >75% of panellists agreed. Results: A panel of 21 expert clinicians from 15 countries provided information from which 83 possible current indicators of damage (kidney, 15; cardiac, 15; CNS/PNS, 13; other, 16; patient reported, 24) were compiled. Of 45 indicators meeting the importance criteria, consensus was reached for 29 and consolidated as 27 indicators (kidney, 6; cardiac, 10; CNS/PNS, 2; other, 6; patient reported, 3) including: (kidney) elevated albumin:creatinine ratio, histological damage, microalbuminuria; (cardiac) markers of early systolic/diastolic dysfunction, elevated serum cardiac troponin; (CNS/PNS) neuropathic pain, gastrointestinal symptoms suggestive of gastrointestinal neuropathy; (other) pain in extremities/neuropathy, angiokeratoma; (patient-reported) febrile crises, progression of symptoms/signs. Panellists revised and approved proposed chronologies of when the consensus indicators manifest. The panel response rate was >95% at all stages. Conclusions: PREDICT-FD captured global opinion regarding current clinical indicators that could prompt FD-specific treatment initiation earlier than is currently practised.